2021
DOI: 10.1038/s41598-021-98016-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fertilizer under different dripline spacings on summer maize in northern China

Abstract: Maximizing grain yields with effective fertilization technologies and minimizing nitrogen losses is essential in agroecosystems. In this research, we conducted a two-year field experiment to explore whether dripline spacing and fertilization rate would affect maize grain yield. Two dripline spacings (i.e., one drip line per row of maize with a row space of 60 cm and one drip line per two rows of maize) and two fertilization rates (i.e., high fertilization level: N, 180 kg ha−1; P2O5, 90 kg ha−1; and K2O, 90 kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 55 publications
(47 reference statements)
1
6
0
Order By: Relevance
“…The remaining pots of tomato plants were harvested after three weeks of water treatment, and different organs (stems and leaves) of one of the tomato plants in each pot were weighed to determine the fresh weight (FW, g•plant −1 ). Next, the materials were placed in an oven, dried at 105 • C for 30 min, and then dried at 75 • C, to a constant weight, for the determination of the dry weight (DW, g•plant −1 ) [32]. The latest, fully expanded leaf of another tomato plant was collected to determine the leaf relative water content (LRWC, %) and leaf relative electrical conductivity (LREC, %) values [33].…”
Section: Sampling and Measurements Of Tomato Shootsmentioning
confidence: 99%
“…The remaining pots of tomato plants were harvested after three weeks of water treatment, and different organs (stems and leaves) of one of the tomato plants in each pot were weighed to determine the fresh weight (FW, g•plant −1 ). Next, the materials were placed in an oven, dried at 105 • C for 30 min, and then dried at 75 • C, to a constant weight, for the determination of the dry weight (DW, g•plant −1 ) [32]. The latest, fully expanded leaf of another tomato plant was collected to determine the leaf relative water content (LRWC, %) and leaf relative electrical conductivity (LREC, %) values [33].…”
Section: Sampling and Measurements Of Tomato Shootsmentioning
confidence: 99%
“…In 2020, China's total consumption of fertilizers reached 45.796 million tons (FAOSTAT, 2022), accounting for 22.8% of the global total consumption, making it the world's largest consumer of fertilizers. The excessive application of fertilizers, however, leads to a series of negative consequences such as the greenhouse effect, groundwater pollution, soil compaction and heavy metal pollution, [3][4][5] threatening the sustainable development of agriculture. In order to address the significant problem of over-fertilization, the Chinese government set a target of zero growth in the use of chemical fertilizers and pesticides in the "13th Five-Year Plan" (2016-2020), and since then, China's fertilizer consumption has entered a new stage of development.…”
Section: Introduction 1background and Motivationmentioning
confidence: 99%
“…Yadvinder-Singh et al 21 suggested that both timing and method of N application are important to increase NUE under straw mulched conditions. Li et al 43 reported that SDI increased the maize grain yield via increased plant nutrient uptake and reduced ammonia volatilization. Reduction in the use of N fertilizer via an increase in the NUE would lead to a substantial reduction in N 2 O emitted from the production and application of N fertilizers 44 .…”
Section: Discussionmentioning
confidence: 99%